2021
DOI: 10.1029/2020tc006271
|View full text |Cite
|
Sign up to set email alerts
|

Exhumation of the Ronda Peridotite During Hyper‐Extension: New Structural and Thermal Constraints From the Nieves Unit (Western Betic Cordillera, Spain)

Abstract: First order non-cylindricity or coexistence of interacting large-scale thrust and extensional shear zones are common features in small orogens hosted in the Mediterranean realm. The tight Betic-Rif arc is typical of this situation where Africa-Eurasia plate convergence strongly interferes with 3-D subduction dynamics to produce a complex crustal-scale tectono-metamorphic evolution (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 191 publications
(552 reference statements)
1
4
0
Order By: Relevance
“…Because apatite grains from Sierra Nevada are fully reset, the partially recrystallized apatite from Sierra de los Filabres and Sierra Alhamilla might indicate that these rocks experienced lower peak temperatures. Similar temperature variations between the Betic orogens have been previously observed in both the NFC and Alpujárride with higher temperatures in the west and lower in the eastern domains (Bessière et al., 2022; Bessière, Augier, et al., 2021; Bessière, Jolivet, et al., 2021; Platt et al., 2006). Additionally, different P / T conditions have also been observed among units in the same localities, which results in a discrepancy among P / T work done in the area as compiled by Santamaría‐López et al.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Because apatite grains from Sierra Nevada are fully reset, the partially recrystallized apatite from Sierra de los Filabres and Sierra Alhamilla might indicate that these rocks experienced lower peak temperatures. Similar temperature variations between the Betic orogens have been previously observed in both the NFC and Alpujárride with higher temperatures in the west and lower in the eastern domains (Bessière et al., 2022; Bessière, Augier, et al., 2021; Bessière, Jolivet, et al., 2021; Platt et al., 2006). Additionally, different P / T conditions have also been observed among units in the same localities, which results in a discrepancy among P / T work done in the area as compiled by Santamaría‐López et al.…”
Section: Discussionsupporting
confidence: 77%
“…After the HP/LT event, fine‐grained Permo‐Triassic schists of the Alpujárride may have experienced 400°C and 0.3–0.4 GPa in the Miocene (Azañón & Crespo‐Blanc, 2000; Bakker et al., 1989; Monié et al., 1991; Platt et al., 2005). Even though the P / T conditions of Alpujárride and the NFC are different, the timing of the metamorphic events is similar (Bessière et al., 2022; Bessière, Augier, et al., 2021; Bessière, Jolivet, et al., 2021). Additionally, Poulaki & Stockli (2022) showed that the NFC and Alpujárride have nearly identical sedimentary provenance signatures and were likely deposited nearby in similar tectonic settings, showing a close affinity between the Internal Betic terranes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bessière, Augier, et al. (2021) recently called for further exploration of this model after reinterpreting a small tectonic window of Blanca‐Unit rocks as a Los Reales klippe (Robledal Klippe).…”
Section: Geological Settingmentioning
confidence: 99%